(untitled) (Polifonia, 1994)
ABSTRACT: This paper examines from a sociolinguistic viewpoint the phonetic productions of five phonemes as wel as some prosodic aspects of the American English spoken by the brazilian actress Sônia Braga in the movie "The Milagro beanfield war", taking as a basis the criticism made by the media of her accent.